The effect of supranational banking supervision on the financial sector: Event study evidence from Europe - Florian Loipersberger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2017)
This paper investigates how the introduction of the Single Supervisory Mechanism, the European Union's implementation of harmonized banking supervision, has affected the banking sector in Europe. I perform an event study on banks' stock returns and find evidence for small but significant positive effects. A potential hypothesis for this result is the fact that a single supervisory authority can take spillover effects between countries into account and is therefore able to stabilize the European banking sector. Splitting the sample by an indicator for supervisory power, an indicator for corruption and by Debt/GDP reveals that the positive impact of the SSM was stronger for banks in countries that perform poorly with respect to these measures.
urn:nbn:de:bvb:19-epub-34610-3
Keywords: G28; H77; F55; 330; banks; event study; supervision; SSM; harmonization